El Salvador : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper proposes a simple nowcast model for an early assessment of the Salvadorian economy. The exercise is based on a bridge model, which is one of the many tools available for nowcasting. For El Salvador, the bridge model exploits information for the period 2005-17 from a large set of variables that are published earlier and at higher frequency than the variable of interest, in this case quarterly GDP. The estimated GDP growth rate in the 4th quarter of 2017 is 2.4 percent year-over-year, leading to an average GDP growth rate of 2.3 percent in 2017. This is in line with the GDP growth implied by the official statistics released two months later, in March 23, 2018.